Numerical Simulation and Experimental Study of the Water-cooled Radiator for High Power Module - WANG Xiaoyuan; WANG Xiong; WANG Xingzhi; MA Bole (Kongzhi Yu Xinxi Jishu)
The performance of water-cooled radiator for the high power module of an electric locomotive’s traction converter was studied based on numerical simulation and experimental study. The results show that the temperature rising and thermal resistance of radiators are obviously different when the models of IGBT are different. The highest thermal resistance of the radiator based on the model of heating module is about 6% higher than the maximum of experimental thermal resistance. The thermal resistance of the radiator decreases as the flow rate of cooling water increases and has no obvious correlation with the variation of the module’s power. The pressure drop of radiator increases as the flow rate of cooling water increases.